Respon Al-Qur’an atas Trend Childfree (Analisis Tafsir Maqāṣidi) - Wijaya, Roma (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2022)
AbstractChildfree, who is committed to withholding children, is seen as the basis for a couple to reach their desired goals, but on the other hand, Indonesian socio-cultural aspects, both legally and culturally, require that they have offspring. From this phenomenon, this article describes the concept of childfree which is responded to by the Qur'an with various interpretations. In this case, the main argument for responding to childfree is Q.S. Ali 'Imran: 38-39 which gives an understanding of the commitment to have children. The theory used in this research is the theory of maqāṣid interpretation analysis which was coined by Abdul Mustaqim. This theory reveals the message behind the meaning of the Qur'an, in this case examining maqāṣid on childfree responses which are considered the principle of freedom. This research is a type of library research that uses data sources in the form of journal articles, books, and other documentary data with the same theme. The results of this study are that there are no specific verses discussing childfree and there are values of maqāṣid that appear, namely hifzhh al-din containing the continuity of religious development, hifzhh al-nasl the existence of gaps that occur in the future, and hifzh al- look at the quality of society and the condition of the people's welfare. AbstrakChildfree yang berkomitmen untuk menahan memiliki anak dipandang sebagai landasan pasutri untuk menggapai cita-cita yang diinginkan, tetapi di sisi lain sosio-kultural Indonesia baik secara undang-undang maupun budaya masyarakat mengharuskan memiliki keturunan. Dari fenomena tersebut artikel ini menguraikan konsep childfree yang direspon oleh Alqurandengan berbagai penafsirannya. Dalam hal ini yang menjadi dalil utama untuk merespon childfree adalah Q.S. Ali ‘Imran: 38-39 yang memberikan pemahaman atas komitmen untuk memiliki keturunan. Adapun teori yang digunakan dalam penelitian ini adalah teori analisis tafsir maqāṣid yang dicetuskan oleh Abdul Mustaqim. Teori ini mengungkapkan pesan dibalik makna al-Qur’an, dalam hal ini mengkaji maqāṣid atas respon childfree yang dianggap sebagai prinsip kebebasan. Penelitian ini berjenis library research yang menggunakan sumber data berupa artikel jurnal, buku, serta data dokumentar lain yang setema. Hasil penelitian ini adalah ayat yang spesifik membicarakan childfree tidak ditemukan dan adanya nilai-nilai maqāṣid yang muncul yaitu hifzh al-din memuat adanya kontinuitas perkembangan agama, hifzh al-nasl adanya kesenjangan yang terjadi di masa depan, dan hifzh al-daulah melihat kualitas masyarakat dan kondisi kesejahteraan rakyat. Kata Kunci: Interpretasi; Ma’na Cum Maghza; QS. Ar-Rahman:33; Sulthan.